Valuation of country of origins of organic processed food: a comparative study of consumer demand for soymilk in the United States and China - Zheng, Yue (Kansas State University, 2011)
The organic food market in the United States expanded rapidly at annual rates between 12% and 21% from 1997 to 2008, yet the adoption rate of organic farming remained stagnant. Industry sources suggest that the degree of outsourcing organic inputs has been increasing during the most recent years. Organic foods are available at traditional supermarkets and mass merchandisers. Many retailers now offer organic food products in their private labels. This study focuses on organic soymilk, which illustrates these recent trends. China, a major low income country which supplies organic agricultural ingredients to the U.S. , has raised food safety concerns fueled by recent incidents. Organic foods have been marketed in China as eco-products in an effort to promote safer foods to meet domestic needs. While organic soybean is one of China’s primary organic exports, China has been the leading importer of conventional soybeans with U.S. as its largest source, but most U.S. production is transgenic. China has a labeling policy on GM (genetically modified) products, which has been more tightly enforced in recent years. This thesis examines U.S. and Chinese consumers’ valuations of attributes of processed organic products, with an emphasis on eliciting their preferences of organic ingredients from different origins, in the case of soymilk. A survey was designed for each country. The U.S. survey was administered online nationwide. An enumerated survey was administered at three types of food retail channels in Beijing, Shanghai and Guangzhou in China. Respectively, 316 and 300 responses were collected from the U.S. and China. Choice experiment was used to elicit consumer values for various attributes of soymilk in both markets. The results show that consumers in both countries are willing to pay premiums for processed foods such as soymilk with organic and non-GMO ingredients. The premium for organic soybeans is significantly higher than that for non-GMO beans. The results also indicate that U.S. consumers hold strong preferences for organic soymilk produced with domestically produced soybeans. In terms of brand preferences, U.S. respondents are willing to pay more for national brands relative to store brands, with taste as a major differentiating factor. In contrast, Chinese consumers’ valuations depend greatly on nationalities of certifying agencies. U.S. certified organic product was perceived higher than EU or Chinese certified organic products, but Chinese-certified non-GMO products were preferred over those certified by U.S. agencies. Chinese consumers’ values varied by cities and retail types where respondents were surveyed.
Keywords: Organic processed food; Willingness to pay estimation; Country of Origins; Comparative study between U.S. and China; Soymilk; Economics, Agricultural (0503)